Determination of the toxicity of zinc sulphate hydrate solution using the Spirotox biotesting method - Kuzmenko, Elizaveta Evgenievna; Hoang, Quynh Thi Ngoc; Koldina, Alena Mikhailovna; Petrov, Gleb Vladimirovich; Syroeshkin , Anton Vladimirovich (Journal of Drug Delivery and Therapeutics, 2025)
Objective: The objective of this study is to determine the toxicity of zinc sulphate hydrate solutions of different forms using the Spirostomum ambiguum.Methods: An experiment was conducted using a solution of the pharmaceutical substances of ZnSO₄·H₂O, ZnSO₄·6H₂O, ZnSO₄·7H₂O. The process of filtration was conducted using a submicron filter. The biological activity of the active pharmaceutical ingredient (API) samples was investigated using the Spirotox method, with the calculation of the activation energy obsEa before and after filtration. An energy dispersive X-ray fluorescence spectrometer was used. The dispersed fraction was subjected to analysis by dynamic light scattering (DLS).Results: The solution of zinc sulphate monohydrate exhibited the highest biological activity and the lowest activation energy (obsEa) of 68±7 kJ/mol. The solutions prepared from zinc sulphate hexahydrate and zinc sulphate heptahydrate displayed obsEa values of 113±5 kJ/mol and 119±5 kJ/mol, respectively, which were found to be equivalent in terms of their biological activity.Conclusion: The findings of the study, conducted using the Spirotox method, revealed that API zinc sulphate, when administered in different forms of hydration, exhibited disparate biological activity despite the identical concentration. The results of the measurements demonstrated that the method of sample preparation of zinc sulphate solutions of equivalent concentration affects the value of the obsEa, which in turn causes different biological activity.Keywords: zinc sulphate, Spirotox-method, activation energy, bioactivity, toxicity.